Analysis of the relationship between knowledge, behaviour, prevention, and self-efficacy on the mental health of athletes during the COVID-19 pandemic - Amiq, Fahrial; Inayatilah, Fidia Rizkiah; Angga, Prayogi Dwina (Universitas Negeri Malang, 2024)
Background: Mental health has become a trending topic during the pandemic. Many athletes have experienced decreased performance during the pandemic, but not a few athletes are able to control their mental health. Objective: The purpose of this study was to examine the relationship between knowledge, preventive behaviour, and self-efficacy on mental health in professional football athletes during the COVID-19 pandemic. This research uses quantitative methods. Methods: This type of research is observational with a cross-sectional study. Eighty professional football athletes were involved in this research. The sampling technique was carried out using a proportional stratified simple random sampling technique. This research was conducted by distributing questionnaires consisting of 4 parts, namely knowledge level questionnaire sheets, preventive behaviour questionnaire sheets, self-efficacy questionnaire sheets, and mental health questionnaire sheets. The data obtained in this study were analyzed using the SPSS application with a descriptive test method to determine the min, max, average, and percentage. Furthermore, data analysis was carried out using the Spearman test method. Results: Based on the results of the study, The low p-value of 0.046 and the correlation coefficient of -0.224 suggest a meaningful negative correlation between self-efficacy and mental health. This indicates that as self-efficacy increases, mental health tends to decrease among the respondents. Conclusion: There is a significant relationship between self-efficacy and the mental health of the respondents. We provide recommendations for Psychologists to develop online interventions that aim to increase individual ability to cope with stressors during a pandemic and reduce excessive perceptions that have a negative impact on mental health.